Protecting Refugee Rights: Legal Perspectives On Asylum and International Protection - Samuel Teja; Amelia Tuku (Proceeding of the International Conference on Law and Human Rights, 2024)
This paper analyzes the legal frameworks governing refugee rights and asylum processes, focusing on the challenges refugees face in seeking protection. By examining case studies from various countries, the research explores issues like legal barriers, discrimination, and access to basic services. The findings highlight the need for stronger international cooperation and legal reforms to ensure the protection of refugees and their human rights.